Emergence of extended spectrum beta-lactamases and carbapenemases producing Klebsiella spp. isolated from Hospital Sultan Abdul Aziz Shah - Muniandy, Vakgesri; Isaac, Sharleen Livina; Amin Nordin, Syafinaz; Song, Adelene Ai Lian; Mohd Hashim, Amalia; Wan Ahmad Kamil, Wan Nur Ismah (Malaysian Society for Molecular Biology and Biotechnology, 2024)
The emergence of extended spectrum β-lactamases (ESBLs) and carbapenemases producing Klebsiella spp. in hospital settings is alarming as it leads to resistance to carbapenems, the last resort of antibiotics. Therefore, the objective of this study is to determine the antibiogram profile and identify the resistance genes present in Klebsiella spp. clinical isolates, encompassing specimens such as urine, sputum, blood and pus. The presence of β-lactamase genes; blaTEM-1 and blaCTX-M-1 and carbapenemases genes; blaNDM-1 and blaVIM-1 were detected by polymerase chain reaction (PCR) analysis. A total of 85 isolates were collected from ill patients at Hospital Sultan Abdul Aziz Shah (HSAAS) between January 2022 and March 2023. The resistance profile of these isolates was analysed using the Kirby-Bauer disk diffusion method against various classes of antibiotics. The results revealed that all 85 Klebsiella spp. tested were resistant to ampicillin and ciprofloxacin. Furthermore, 78% of isolates were resistant to cephalosporins, suggesting that these strains were producing ESBLs. In terms of carbapenem resistance, the isolates were more resistant towards meropenem (80%) than imipenem (60%). These 85 clinical isolates were also resistant to kanamycin (52%). The presence of blaTEM-1 and blaCTX-M-1 genes were detected in the tested isolates, namely strain number 15,18,27,64 and 65. Moreover, the carbapenem-non-susceptible isolates were detected to have blaNDM-1 and blaVIM-1 genes. These findings highlighted a substantial proportion of isolates as ESBLs and carbapenemase producers. In conclusion, this study emphasised the urgent need for enhanced surveillance programs to combat the escalating threats of multidrug resistance Klebsiella spp. in clinical settings. Additionally, routine molecular screening for resistance genes along with rapid diagnostics for detecting these genes, should be implemented to enable doctors to prescribe the correct antibiotic.